Quality of work life (QWL) and riding behaviour among civil servants in Klang Valley - Jaafa, Noor Hidayah; Rasdi, Irniza; Mohamad, Nur Jamima; Darus, Azlan; Bakar, Harun (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: The number of road accidents involving workers was on the rise, with more than 30,000 cases recorded and 76.9% involved motorcyclists and pillion riders. Despite of numerous studies have been conducted to explore the causes of this worrisome condition, little is known on the influence of working quality to riding behaviour. Methods: This cross-sectional study involved 187 riders (male: 66.3%; female: 33.7%) with average age was 33 years were randomly selected civil servants in Putrajaya, Kuala Lumpur, and Selangor. Self-administered questionnaire was used to collect information on socio-demographic and working background, riding experience, quality of working life (WRQoL) and riding behaviour (SMRBQ). Results: The most prevalent unsafe riding behaviour reported was tailgating the vehicles in front (88.2%) and speeding (70.6%). In multiple linear regressions, being male (β = 0.16, p = 0.03), type of motorcycle (β = 0.14, p = 0.04), and stress at work (β = 0.20, p < 0.01), predict erroneous riding. Whereas, lower educational level (β = 0.17, p = 0.02), stress at work (β = 0.19, p = 0.01), and lower job satisfaction (β = 0.15, p = 0.04) predict poorer helmet use behaviour. Also, male and younger riders reported to have higher level of time and money opportunistic riding behaviour. Conclusion: Findings of the study suggests that riding behaviour can be improved by increasing the quality of working life among workers such as work related stress, job satisfaction and also control at work. Thus, program planner should consider WRQoL in designing intervention related to road safety program.